HUBUNGAN CITRA TUBUH, AKTIVITAS FISIK DAN PENGETAHUAN GIZI SEIMBANG DENGAN KEJADIAN OBESITAS PADA REMAJA PUTRI GIZI LEBIH DI SMA NEGERI 9 KOTA SEMARANG - Meylda Intantiyana; Laksmi Widajanti; M . Zen Rahfiludin (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Adolescent girls are the vulnerable group for nutritional problems. Nutritional problems in adolescent girls can be caused by a strict diet, poor eating habits, lifestyle, infectious diseases, self-assessment (body image), physical activity carried out and knowledge of balanced nutrition. The purpose of this study was to analyze the correlation between body image, physical activity, and balanced nutrition knowledge with the incidence of obesity among overweight girls.This study was an observational study using a cross-sectional design. The subjects were 67 female students chosen through total sampling. Data were collected through interviews using structured questionnaires and physical activity 24 hours recall, weight and height measurements and analyzed using Chi-Square Test. The data collected were the characteristics of adolescent girls, nutritional status based on z-score BMI for age, body image, physical activity and student knowledge about balanced nutrition.The results showed that most of the subjects were obese (65.7%), had positive body image (53.7%), had mild physical activity (52.2%), and had good knowledge nutrition (70,1%). There was a significant correlation between positive body image (p=0.008), mild physical activity (p=<0.001) with the incidence of obesity. There was no correlation between balanced nutrition knowledge (p=0.837) with the incidence of obesity among overweight girls. It is concluded that positive body image and mild physical activity, were related to obesity incidence..